2011
DOI: 10.1080/17461391.2011.566367
|View full text |Cite
|
Sign up to set email alerts
|

Culture, individual differences, and situation: Influence on coping in French and Chinese table tennis players

Abstract: The aim of the present study was to explore the influence of culture, individual differences (i.e. trait emotional intelligence), and given situations on coping behaviours. The trait emotional intelligence of table tennis players (French, n 058; Chinese, n 053) was evaluated using the Trait Emotional Intelligence Questionnaire, while their use of coping strategies [taskoriented coping (TOC) and disengagement-oriented coping (DOC)] was assessed according to three stressful situations. There was a main effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
3
22
1
2
Order By: Relevance
“…The main difference between the two studies was during the MAJ competition in which the tenpin bowlers used more AVC and less PFC when compared to the runners. Findings are not in agreement with Laborde et al (2012) who found that Chinese table tennis players used more PFC and AVC than the French players. This suggests that differences in coping are more likely the result of the importance of the context (importance of the competition) and the stressor experienced rather than cultural or ethnic differences.…”
Section: Stressorscontrasting
confidence: 56%
See 1 more Smart Citation
“…The main difference between the two studies was during the MAJ competition in which the tenpin bowlers used more AVC and less PFC when compared to the runners. Findings are not in agreement with Laborde et al (2012) who found that Chinese table tennis players used more PFC and AVC than the French players. This suggests that differences in coping are more likely the result of the importance of the context (importance of the competition) and the stressor experienced rather than cultural or ethnic differences.…”
Section: Stressorscontrasting
confidence: 56%
“…A study on Korean athletes found an additional coping dimension called "transcendental coping" (Yoo, 2001). Similarly, Laborde, You, Dosseville, and Salinas (2012) found that Chinese table tennis players used more frequently task-oriented and disengagement-oriented coping strategies than their French counterparts. There is also evidence that culture is an important factor in shaping emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to translate the Chronotype Questionnaire, guidelines from van de Vijver and Hambleton (1996) were followed, as it has already been done in previous research (e.g., Laborde et al, 2012). A double back-translation procedure was used to adapt the questionnaire from English to French.…”
Section: Questionnaire: the Chronotype Questionnairementioning
confidence: 99%
“…We identified three studies that had explored EI as it relates to psychological skill usage (Lane et al., ; Kajbafnezhad et al., ; Laborde et al., ). In each case, a higher trait EI was found to relate to a more frequent use of psychological skills.…”
Section: Sport Performancementioning
confidence: 99%